CLINICAL AND IMMUNOLOGICAL FEATURES OF OMALIZUMAB TREATMENT OF ATOPIC BRONCHIAL ASTHMA IN UZBEKISTAN (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The aim of the study was to study the effect of Omalizumab on clinical and im-munological parameters in patients with atopic bronchial asthma in Uzbekistan. Materials and methods. 36 patients with atopic bronchial asthma who were administered Omalizumab at a dose of 150 mg (Novartis, Norway) were examined. Before and after treatment, patients underwent a general blood test, total IgE and immune status, including determination of the level of lymphocytes, CD3, CD4, CD8, CD16, CD20, CD23, CD25, CD95 subpopulations. Results. During treatment with Omalizumab for atopic asthma, there was a tendency to decrease ESR, relative eosinophil count, significant decrease in leuko-cyte count, absolute eosinophil count, significant decrease in absolute CD8, CD16, and CD23 counts, and an increase in total IgE. Conclusions: 1. The use of Omalizumab in patients with atopic asthma leads to a decrease in the content of eosinophils and leukocytes. 2. Omalizumab reduces CD8, CD16, and CD23 levels in atopic asthma. 3. A single application of Omalizumab leads to an increase in the level of total IgE in patients with atopic asthma with clinical improvement.